2017
DOI: 10.3389/fimmu.2017.01772
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Stimulator of Interferon Genes As a Robust Adjuvant Target for Early Life Immunization

Abstract: Immunization is key to preventing infectious diseases, a leading cause of death early in life. However, due to age-specific immunity, vaccines often demonstrate reduced efficacy in newborns and young infants as compared to adults. Here, we combined in vitro and in vivo approaches to identify adjuvant candidates for early life immunization. We employed newborn and adult bone marrow-derived dendritic cells (BMDCs) to perform a screening of pattern recognition receptor agonists and found that the stimulator of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(69 citation statements)
references
References 68 publications
4
64
0
1
Order By: Relevance
“…Our observations regarding the phenotype of DC subsets in neonatal murine lungs indicated an intrinsic age-specific difference in the percentages and maturation status of migratory APC subsets, raising the possibility that functional responses of migDCs subsets to stimuli such as PRR agonist adjuvants may also be distinct. To test this hypothesis, we stimulated CD11c + cells isolated from the lungs of different aged mice and stimulated them with different classes of PRR receptor agonists at a concentrations reported most active for bone marrow DC activation (24,25). We then summarized the combined flow cytometry all APCs maturation data collected following ex vivo stimulation, and graphed the data as volumetric dot sizes indicating the relative fold change (ranging form < 1 to > 4.5) for CD40, CD80 and CD86, per F4/80, CD11b, CD103 PDCA-1 APC subsets, as compared with un-stimulated controls per age group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our observations regarding the phenotype of DC subsets in neonatal murine lungs indicated an intrinsic age-specific difference in the percentages and maturation status of migratory APC subsets, raising the possibility that functional responses of migDCs subsets to stimuli such as PRR agonist adjuvants may also be distinct. To test this hypothesis, we stimulated CD11c + cells isolated from the lungs of different aged mice and stimulated them with different classes of PRR receptor agonists at a concentrations reported most active for bone marrow DC activation (24,25). We then summarized the combined flow cytometry all APCs maturation data collected following ex vivo stimulation, and graphed the data as volumetric dot sizes indicating the relative fold change (ranging form < 1 to > 4.5) for CD40, CD80 and CD86, per F4/80, CD11b, CD103 PDCA-1 APC subsets, as compared with un-stimulated controls per age group.…”
Section: Resultsmentioning
confidence: 99%
“…All PRR agonists employed in the studies were verified endotoxin-free as indicated by the manufacturers (Invivogen). For stimulation experiments, isolated lung CD11c + cells from newborn and adult mice were plated in round bottom 96-wells non-tissue culture-treated plates at the density of 10 5 cells/well in 200 µl of fresh complete culture medium and were stimulated with 100 ng/ml of PAM3CSK4, PAM2CSK4, Poly I:C, MPLA, S. typhimurium Flagellin, 5’ppp-dsRNA, or 0.1 μM of CL075, CpG class C - ODN 2395 100 μg/ml of 2’3’-cGAMP as previously described (24,25). All Abs used for flow cytometry are listed in Table S1.…”
Section: Methodsmentioning
confidence: 99%
“…Blood samples were collected by retroorbital bleeding on day +14 (pre-boost) and day +28, and plasma was isolated after centrifugation of blood samples at 500 g for 20 minutes. rHA-specific IgG, IgG1, IgG2c antibody titers were quantified in plasma samples by ELISA as previously described (49). Briefly, high binding flat bottom 96-well plates were coated with 1 µg/ml rHA in carbonate buffer pH 9.6, incubated overnight at 4°C and blocked with PBS + BSA 1% for 1 h at room temperature.…”
Section: Discussionmentioning
confidence: 99%
“…One modeling study showed that for every doubling of Ab by a vaccine, severe disease may be reduced by 30% and protection prolonged for an additional 50 days. Maternal immunization is an attractive option, and a number of vaccine candidates are under development and evaluation (15,17). Factors that are important to consider for candidate vaccines include how much Ab is generated in the mother, the variability of the response, the best gestational age to vaccinate, the protection of the mother, the placental transfer of Ab, the impact of breast feeding, the persistence of the presence of passively acquired Abs, the possible interference with infant response to natural infection, and the potential effect of delaying the age of infection to later in childhood.…”
Section: Update On Vaccines Under Development For Maternal and Neonatmentioning
confidence: 99%
“…Carlo Pietrasanta (Boston Children's Hospital and Harvard Medical School, USA) reported that certain combinations of Stimulator of Interferon Genes (STING) and Toll-like receptor (TLR) agonists act in synergy to activate Th1-polarizing responses from human neonatal antigen-presenting cells, suggesting that STING agonists, alone or combined with alum and/or TLR agonists, may be candidate adjuvants for early life immunization (15). Selena Alonso (Barcelona Institute for Global Health, Spain) discussed the impact of maternal infections on infant responses to vaccines.…”
mentioning
confidence: 99%